2018
DOI: 10.3390/land7040130
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Functionality in Participatory Integrated Watershed Development of Tana Sub-Basin, Ethiopia

Abstract: Sustaining watersheds that were developed through community mobilization are a major challenge in Ethiopia despite significant efforts to promote soil and water conservation technologies and approaches. This paper investigates the hypothesis that institutional rationality and functionality play an important role in developing enduring watersheds by comparing the good performing Model research watersheds and adjacent watersheds developed through extensively promoted community mobilization. A semi-qualitative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, members of natural resource conservation committees do not enforce community regulations, resulting in the unsustainable nature of the established land management practices. Tesfaye et al [22], in agreement with this finding, addressed how the lack of robust enforcement from watershed committees contributed to the ineffectiveness of watershed management strategies. Participants in the focus group discussion and key informants also revealed that there is a gap in successfully enforcing community regulations because the community is sometimes uncooperative.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, members of natural resource conservation committees do not enforce community regulations, resulting in the unsustainable nature of the established land management practices. Tesfaye et al [22], in agreement with this finding, addressed how the lack of robust enforcement from watershed committees contributed to the ineffectiveness of watershed management strategies. Participants in the focus group discussion and key informants also revealed that there is a gap in successfully enforcing community regulations because the community is sometimes uncooperative.…”
Section: Discussionmentioning
confidence: 85%
“…Various soil and water conservation practices, such as the use of stone terraces, soil bunds and area closures, which are implemented with the support of external aids and donors, are limited to bring the expected results on land resources and the livelihoods of people [20]. According to Sileshi et al [21] and Tesfaye et al [22], though there were various efforts towards improving land management practices, the problem of land degradation remains a serious challenge. Land management practices mostly comprised seasonal campaigns, and the measure of success was more in terms of area coverage than the quality of measures to bring about the intended benefits, and this made the practices unsustainable [19,23].…”
Section: Introductionmentioning
confidence: 99%
“…Watershed groups: Rural community organized in groups through community mobilization to promote soil and water conservation technologies and approaches [112]. Groups are organized in village based on their daily interaction in the village, and peoples who are settled in one area organized into the same groups [113].…”
Section: 4indigenous Mutual Support Informal Institutions Social Netw...mentioning
confidence: 99%